Einfluss atmosphärischer Umgebungsbedingungen auf den Lebenszyklus konvektiver Zellen in der Echtzeit-Vorhersage - Wilhelm, Jannik (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2022)
Precise warnings of the accompanying effects of thunderstorms are essential for preventive measures. The dynamic development of thunderstorm cells often leads to a large discrepancy between the real-time forecasts (nowcasts) of weather services and the observed weather conditions. Data from a cell tracking algorithm are combined with model analyses to investigate the life cycle of thunderstorms in Germany and to develop and evaluate procedures useful for thunderstorm nowcasting.